Pengaruh Pengumuman Right Issue Terhadap Return Saham, Abnormal Return, Frekuensi Perdagangan, Volume Perdagangan, Risiko Saham dan Kapitalisasi Pasar Pada Perusahaan Property, Real Estate and Building Construction yang Terdaftar di BEI Tahun 2008-2011 - Ryan Patria Ruli; Emrinaldi Nur Dp; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine whether there are differences in stock returns, abnormal returns, trading frequency, trading volume, stock risk and the market capitalization before and after the announcement of the rights issue. This research applied in property, real estate and building construction which listed on the Indonesian Stock Exchange 2008-2011 periods. This research for was conducted with the event study. Porposive sampling use as sampling technique. The study was conducted on 36 companies. Independent sample t-test used to examine differences in stock returns, abnormal returns, trading frequency, trading volume, stock risk and the market capitalization before and after the announcement of the rights issue. Based on the results of testing the hypothesis, this study showed that the have a significant difference stock returns , abnormal returns, stock risk and the market capitalization before and after the announcement of the rights issue ( with α = 5 % ) have no significant difference in right issue the average trading frequency and trading volume right issue.Keywords : rights issue, stock returns, abnormal returns, trading frequency, trading volume, stock risk, the market capitalization.